1982
DOI: 10.1021/bi00541a033
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of the equilibrium between two nucleotide-free myosin subfragment 1 states using fluorine-19 NMR

Abstract: A new fluorine-containing reagent has been synthesized and used to specifically label the reactive sulfhydryl [sulfhydryl-1 (SH1)] of myosin subfragment 1 (S-1). The labeled S-1 (S-1-CF3) demonstrates activated calcium and magnesium adenosinetriphosphatase (ATPase) activities relative to S-1 and a lower potassium ethylenediaminetetraacetate (EDTA) ATPase activity. Maximal effect is obtained with the modification of one thiol per S-1. The 19F NMR spectrum of S-1 CF3 contains only one resonance with a line width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…These data have been interpreted as indicating that the myosin heads exist as an equilibrium mixture of two conformational states even when they do not interact with nucleotide or actin [17]. Such a possibility has also been considered on theoretical grounds [18] and has found experimental support from the effects of nucleotides and temperature on the I9F-NMR spectrum of a fluorine probe attached to the SH1 thiol group in rabbit skeletal muscle S1 [19, 201. It has been suggested that the conformational distortions underlying the myosin head alternation between the weak and strong actin binding states in the crossbridge cycle [21] resolve themselves into nucleotide-and actininduced shifts in the equilibrium between the two intrinsic states of the head [17-201.…”
mentioning
confidence: 99%
“…These data have been interpreted as indicating that the myosin heads exist as an equilibrium mixture of two conformational states even when they do not interact with nucleotide or actin [17]. Such a possibility has also been considered on theoretical grounds [18] and has found experimental support from the effects of nucleotides and temperature on the I9F-NMR spectrum of a fluorine probe attached to the SH1 thiol group in rabbit skeletal muscle S1 [19, 201. It has been suggested that the conformational distortions underlying the myosin head alternation between the weak and strong actin binding states in the crossbridge cycle [21] resolve themselves into nucleotide-and actininduced shifts in the equilibrium between the two intrinsic states of the head [17-201.…”
mentioning
confidence: 99%
“…However, the results obtained with various techniques differ with regard to the direction of the temperatureand nucleotide-induced alterations. The changes in the hydrogen-exchange rate of tryptophan residues [57], ultraviolet absorption [56], and EPR spectra of spin-labeled heavy meromyosin or myosin [35, 581 that occur on elevation of temperature were qualitatively similar to those induced by MgADP or MgAdoPP[NH]P. The 19F-NMR spectra of a fluorine probe attached at the SH1 thiol group indicated, on the contrary, that the low-temperature state of S1 is identical to that predominating in the presence of MgADP or MgAdoPP[NH]P at 25°C [55]. Our results are in accord with the latter observation.…”
Section: Discussionmentioning
confidence: 99%
“…The results have been interpreted as indicating that the myosin head itself exists in two conformational states in equilibrium which depends on ambient factors and is perturbed by the binding of nucleotides [36, 37, 52, 541. Evidence supporting this conclusion has been provided by studies of 19F-NMR spectra of a fluorine-containing probe attached to the SH1 thiol group of S1 [55] and ultraviolet absorption [56], hydrogen-deuterium exchange [57] and spin-label studies on heavy meromyosin [58]. Geeves et al [59] and Shriver [54] have recently reviewed and discussed kinetic evidence for two types of ternary complexes of myosin with nucleotide and actin which differ in the affinity between myosin and actin.…”
mentioning
confidence: 99%
“…Conformational changes within the myosin head during steady-state ATP hydrolysis have been detected by observing changes in the UV absorbance [53], intrinsic fluorescence [30,31,54], biochemical crosslinking [55,56], electron paramagnetic resonance spectroscopy [57][58][59], electron microscopy [60][61][62], NMR spectroscopy [63], fluorescent labeling [64], fluorescence energy transfer [65], small-angle X-ray scattering [66]. In addition, fluorescence polarization is highly sensitive to conformational changes in myosin [67][68][69].…”
Section: Conformational Studies Of Myosin S1mentioning
confidence: 99%